Pengaruh Karakteristik Pekerjaan dan Komitmen Organisasi terhadap Motivasi dan Dampaknya terhadap Kinerja Pegawai pada Sekretariat Daerah Kabupaten Tanjung Jabung Timur - Heri Ahmadi; Osrita Hapsara; Sudirman Sudirman (J-MAS (Jurnal Manajemen dan Sains), 2023)
The level of work characteristics of organizational commitment, work environment and motivation for employee performance at the Regional Secretariat of Tanjung Jabung Timur Regency based on data from the analysis The influence of work characteristics directly on the work motivation of employees at the Regional Secretariat of Tanjung Jabung Timur Regency has a positive and significant effect. I This means that the characteristics of the work have the potential to provide a working mechanism so as to create a better work drive.The influence of direct organizational commitment on the work motivation of employees at the Regional Secretariat of Tanjung Jabung Timur Regency has a positive and significant effect. This means that organizational commitment can provide a passion for work, therefore with a better organizational commitment, employees will be more encouraged to work The influence of direct organizational commitment on employee performance at the Regional Secretariat of Tanjung Jabung Timur Regency has a positive and significant effect. This means that organizational commitment that is conducive, adequate, and supports better task execution can improve the performance of employees. The results of simultaneous testing, it was proven that from the three independent variables tested for their effect on performance, it turned out that motivation had a more dominant influence on employee performance at the Regional Secretariat of Tanjung Jabung Timur Regency. It gives meaning that, the existence of responsibility, having targets, having goals, feedback, feelings of pleasure, competition, achievements, needs, rewards, incentives, and relationships between each other can improve the performance of employees at the Regional Secretariat of Tanjung Jabung Timur Regency in carrying out daily work activities